The Subnational Dimension of Europeanization - Dobrić Jambrović, Dana; Marešić, Mariela (Review of European and Comparative Law, 2020)
Despite the increasing influence of European legislation on the subnational level of government and local public policy, until recently, the subnational level has played only a marginal role in exploring Europeanization processes. With the creation of the single market in the early 1990s, the process of European integration began to have a significant impact on local governments across Europe. Subsequently, the development of European regional and cohesion policy resulted in the adaptation of the political and administrative structures of the local units of the Member States. However, the impact of European integration is not one-sided. The European Union's multilevel governance system and the spread of the impact of Europeanization on interstate levels pose new challenges for European cities and local actors and enable them to actively participate and influence political decision-making processes at the European level. The paper first conceptualizes the phenomenon of Europeanization and then identifies and addresses its dimensions and mechanisms in the field of local self-government. Emphasis is placed on the implementation of European legislation by local authorities and the institutional and non-institutional (indirect and direct) participation of subnational units in European governance. In an attempt to provide answers to the research questions, the author used the legal analysis and the teleological and linguistic method.